2016
DOI: 10.1111/epi.13582
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of posttraumatic seizures following traumatic brain injury: A Traumatic Brain Injury Model Systems Study

Abstract: SUMMARYObjective: Determine incidence of posttraumatic seizure (PTS) following traumatic brain injury (TBI) among individuals with moderate-to-severe TBI requiring rehabilitation and surviving at least 5 years. Methods: Using the prospective TBI Model Systems National Database, we calculated PTS incidence during acute hospitalization, and at years 1, 2, and 5 postinjury in a continuously followed cohort enrolled from 1989 to 2000 (n = 795). Incidence rates were stratified by risk factors, and adjusted relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
95
5
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 49 publications
(108 reference statements)
17
95
5
7
Order By: Relevance
“…2 PTE rates are reported in up to 20% of patients, with increased risk based on brain injury severity, surgical intervention, time since traumatic brain injury (TBI), and younger age. [3][4][5][6] Although some risk factors are known, we need to better stratify patients at highest risk for PTE to better understand antiepileptogenesis and develop therapeutic agents. Although there is great interest in interventions to prevent post-TBI epileptogenesis, clinical trials have been plagued by financial and logistical barriers, with estimates upward of $20 million.…”
mentioning
confidence: 99%
“…2 PTE rates are reported in up to 20% of patients, with increased risk based on brain injury severity, surgical intervention, time since traumatic brain injury (TBI), and younger age. [3][4][5][6] Although some risk factors are known, we need to better stratify patients at highest risk for PTE to better understand antiepileptogenesis and develop therapeutic agents. Although there is great interest in interventions to prevent post-TBI epileptogenesis, clinical trials have been plagued by financial and logistical barriers, with estimates upward of $20 million.…”
mentioning
confidence: 99%
“…Being able to monitor brain health and the development of seizure activity is particularly useful after a traumatic brain injury 2,3 . After injury, putting electrodes, such as ECoG arrays, within the cranial cavity could potentially compound the injury by causing additional irritation and damage 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The ability to chronically monitor brain health and watch for epileptic activity development would be quite useful after brain trauma or surgery 2,3 . However, continuous brain monitoring via scalp surface electroencephalograms (EEGs) can be cumbersome and impractical outside of the clinical setting and may not be possible if the skin is not healthy enough after injury to safely apply the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Post‐traumatic seizures are an important complication of head injury, and can be classified as immediate (occurring within 24 hours of injury), early (occurring between 24 hours and one week of injury), or late (occurring more than 7 days following injury). Late post‐traumatic seizures are often taken to indicate the presence post‐traumatic epilepsy . In a large US epidemiological study, the five‐year cumulative incidence of post‐traumatic seizures was reported to be 0.7, 1.2, and 10% in mild, moderate and severe head injuries respectively and more recent studies have reported the cumulative prevalence of post‐traumatic seizures to range between 4 and 20.5% .…”
Section: Introductionmentioning
confidence: 99%
“…Late post‐traumatic seizures are often taken to indicate the presence post‐traumatic epilepsy . In a large US epidemiological study, the five‐year cumulative incidence of post‐traumatic seizures was reported to be 0.7, 1.2, and 10% in mild, moderate and severe head injuries respectively and more recent studies have reported the cumulative prevalence of post‐traumatic seizures to range between 4 and 20.5% . Following traumatic brain injury, the risk of developing epilepsy may be as much as 30 times higher than in the general population, and the majority of patients who develop post‐traumatic epilepsy after TBI have drug‐resistant epilepsy, which means that they fail to respond to an adequate trial of more than two appropriately selected anti‐epileptic drugs .…”
Section: Introductionmentioning
confidence: 99%